Jabatan Imigresen Malaysia Negeri Johor Darul / Farzana Afrina Mohd Sar - Mohd Sar, Farzana Afrina (Faculty of Business and Management, 2025)
The Jabatan Imigresen Malaysia Negeri Johor is responsible for administering immigration affairs in one of Malaysia's most strategically significant states. The immigration department holds a major responsible in charge of border control, visa processing, and foreign worker management in Johor. It handles millions of border crossings each year, primarily at the busiest Johor-Singapore borders. The key priorities of the Johor immigration can include expediting immigration procedures, combatting human trafficking, and adjusting to the changing requirements of Johor's expanding economy and tourist industry. In addition, this report will focus on the perspectives of the human resources department since during my internship, I was assigned to this department. Other than that, this industrial training report will also focus on the SWOT analysis of Jabatan Imigresen Malaysia Negeri Johor. This segment will help to identify the significance that is within the Jabatan Imigresen Malaysia Negeri Johor. As one of the company’s strengths is its implementation of technological advancements, which help the department to operate efficiently and have no more delays. Meanwhile, the weakness that I have observed in the human resource department is limited space and storage, which increases the chance of document misplacement. On the other hand, the external factors, discussions, and recommendations are highlighted in this report to conclude the findings.